2019
DOI: 10.1016/j.compstruct.2018.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term thermal cycling and moisture on heated Fibre Metal Laminates and glass-fibre epoxy composites

Abstract: Heated GLARE, a Fibre Metal Laminate with an integrated heater element, has a promising potential as de-or anti-icing system in aircraft structures. To investigate the long-term durability of heated GLARE previously reported thermal cycling tests up to 12000 cycles are extended up to 144000 cycles and moisture conditioning is included. Similar testing up to 72000 cycles is performed on FM906 glass-fibre epoxy laminates with an integrated heater element to study the influence of the aluminium layers in GLARE.In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(22 reference statements)
2
8
0
Order By: Relevance
“…Similar trends have been observed in authors previous studies for laminates with a different method of aluminium surface preparation [12,19] and in hygrothermal conditions by da Costa [20]. Significant effects of thermal shocks on GLARE [15,[31][32][33] and CARALL [34,35] laminates were only observed after more than 10,000 thermal cycles. The lack of significant difference in interlaminar shear strength of the tested laminates results from the very low thickness of glass layers and effectively limiting degradation of the metal/composite interface.…”
Section: Static Interlaminar Shearsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar trends have been observed in authors previous studies for laminates with a different method of aluminium surface preparation [12,19] and in hygrothermal conditions by da Costa [20]. Significant effects of thermal shocks on GLARE [15,[31][32][33] and CARALL [34,35] laminates were only observed after more than 10,000 thermal cycles. The lack of significant difference in interlaminar shear strength of the tested laminates results from the very low thickness of glass layers and effectively limiting degradation of the metal/composite interface.…”
Section: Static Interlaminar Shearsupporting
confidence: 89%
“…Kubit et al [44] observed a decrease in stiffness and ILSS after the thermal cycling of fibre metal laminate made of prepregs with twisted yarn and aluminium alloy 2024-T3. Also, Hagenbeek et al [31] observed a significant (in the range of 10-30%) decrease of ILSS after long-term thermal cycling of a fibre metal laminate reinforced by glass fibres. In the current research, also a similar significant decrease of stiffness and static ILSS (in the range of 7-12%) was observed in laminates with additional layers of glass fibres.…”
Section: Fatigue Lifementioning
confidence: 98%
“…In all reported test results the maximum decrease in interlaminar shear strength (ILSS) after thermal cycling was found in the first stage from 0 to 10,000 cycles (-32.9% for heated GLARE cycled between -20 and 50 • C). This initial drop in strength was followed by a recovery phase and a resumed decline after roughly 60,000 cycles [3]. No crack or voids or other visible changes were found in the optical microscope images and the drop is expected to be caused by internal stress relief.…”
Section: Introductionmentioning
confidence: 91%
“…In previously reported research the effect of thermal cycling and moisture on heated GLARE has been examined separately and in combination with each other [1,2,3]. The effect of additional static loading was however not yet considered in these investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Müller [ 22 ] designed a thermal cycling setup to investigate the effects of thermal cycling on the material properties of GLARE and found out the interlaminar shear strength increased with the number of cycles. Hagenbeek [ 23 ] conducted experiments of long-term thermal cycling and moisture on heated fiber metal laminates and glass-fiber epoxy composites to research the durability of structure. Subsequently, Hagenbeek [ 24 ] studied the effects of thermal cycling on heated fiber metal laminates under static load.…”
Section: Introductionmentioning
confidence: 99%